SIFAT OPTIK Zinc Oxide (ZnO) YANG DIDEPOSISI DI ATAS SUBSTRAT KACA MENGGUNAKAN METODE CHEMICAL SOLUTION DEPOSITION (CSD) DAN APLIKASINYA UNTUK DEGRADASI ZAT WARNA METHYLENE BLUE - Agustya Tri Surono; Heri Sutanto (Youngster Physics Journal, 2014)
In this research, ZnO thin films have been successfully deposited on glass substrates by spray coating technique with a variety of solution concentration 0,3M, 0,5M, 0,75M and 0,9M. Optical properties ZnO thin films were characterized by using UV-Vis spectroscopy. Methylene blue as degradation media was used to estimate the photocatalytic activity from deposition samples ZnO. The research showed that the greater the concentration of the deposition solution in the absorption value increases, the transmittance decreases and getting smaller value of the band gap energy. Assay results photocatalytic activity of ZnO was able to degrade methylene blue to 96.6%.Keywords: Photocatalyst, Spray coating, ZnO, Band gap energy, Methylene blue.